The fatty acid profile of Serbian bee-collected pollen – a chemotaxonomic and nutritional approach. Issue 5 (20th October 2017) - Kostić, Aleksandar Ž; Pešić, Mirjana B; Trbović, Dejana; Petronijević, Radivoj; Dramićanin, Aleksandra M; Milojković-Opsenica, Dušanka M; Tešić, Živoslav Lj
Abstract : The fatty acid profile, its relation to botanical origin and nutritional characteristics of bee-collected pollen from Serbia was determined. Twenty different fatty acids were detected. Depending on the palynological origin, the fatty acid (FAs) composition varied greatly. Three groups of pollen samples can be differentiated on the basis of Categorical principal component analysis. The first group was characterized by the presence of Fraxinus sp. pollen as predominant type and Zea mays as an accompanying pollen type and a high level of polyunsaturated FAs. Rannunculaceae, Apiaceae and Asteraceae family pollen, Ambrosia, Plantago, Sophora and Helianthus annuus pollen influenced the presence of saturated FAs and separation of the second group of samples. Pollen of plants belonging to the Fabaceae and Brassicaceae families had significant influence on constitution of the third group of samples with saturated and unsaturated FAs. The most abundant saturated, mono- and poly unsaturated fatty acids were palmitic, oleic and linolenic acid, respectively.